WS: Shared Visions: Marco Polo’s travels from Medieval collective imagination to contemporary computer-assisted imagery - Federico Boschetti (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
In this workshop, participants explore the intersection between Medieval and contemporary representations of Marco Polo's travels. The discussion focuses on the creation of an interactive exhibition where visitors engage with miniatures from MS. Bodl. 264. By selecting specific details from these miniatures, visitors describe them for targeted audiences—such as children, the elderly, or visually impaired people. These descriptions, combined with AI, generate new images inspired by the originals and the participants' unique perspectives. This process blends historical collective imagination with modern, computer-assisted creativity, inviting new interpretations of Marco Polo’s legacy.